Implementation of School Literacy Movement in Islamic Primary School Al Istiqomah - Ulpiah Ulpiah; Siti Khozanatu Rohmah; Asis Saefudin (Al-Aulad: Journal of Islamic Primary Education, 2022)
SDIT Al-Istiqomah is a school that has programs and achievements in the field of literacy, so it is interesting to study how to implement the school literacy movement in the elementary school, including the obstacles and solutions. The method used in this research is the case study method. Based on the results of the study, the implementation of the school literacy movement was carried out in the stages of planning, implementation, and evaluation. At the implementation stage, it is divided into three parts, namely habituation, development, and learning. The various activities are reading, reviewing, presenting, selecting reading ambassadors, and training. The obstacles faced were limited time, difficulty in retelling the contents of reading, and decreased interest in reading during the pandemic. The solution to overcome this is literacy extracurricular activities, providing motivation, and collaboration with parents